Sepsis in the older person. (2nd August 2021) - Conner, Tony; Thompson, Juliana; Tiplady, Sue
Abstract : Background: Sepsis is a common condition, with an estimated 30 million cases worldwide each year, resulting in 6 million sepsis-related deaths. Some 60% of all sepsis events and 80% of sepsis-associated deaths occur in the older population. This is because the ageing process, and the presence of multiple comorbidities, make many older people vulnerable to developing, and dying from, sepsis. However, serious illness and death from sepsis can be avoided if the signs and symptoms are identified quickly, and interventions started early. Methods: This article explains current research and guidelines with regard to the causes, recognition, treatment and prevention of sepsis in the older population, and considers the role of care home staff in supporting effective care of residents as risk of developing sepsis. Conclusions: Care home staff are well-positioned to recognise sepsis and contribute to treatment, as their in-depth knowledge of residents makes it easier for them to identify changes in residents' behaviours and health status, which may indicate sepsis. By taking steps to ensure the risk of developing infections is reduced, care home staff can make a valuable contribution to the prevention of sepsis.